Associations between comorbidities and immediate and one-year outcomes following supervised exercise therapy and patient education – A cohort study of 24, 513 individuals with knee or hip osteoarthritis. Issue 1 (January 2021) - Pihl, K.; Roos, E.M.; Taylor, R.S.; Grønne, D.T.; Skou, S.T.
Summary: Objective: To investigate if comorbidities are associated with change in health outcomes following an 8-week exercise and education program in knee and hip osteoarthritis (OA). Methods: We included 24, 513 individuals with knee or hip OA from the Good Life with osteoArthritis in Denmark (GLA:D®). GLA:D® consists of two patient education sessions and 12 supervised exercise sessions. Before the program, individuals self-reported having one or more of 11 common comorbidities. Physical function was assessed using the 40-m Fast-Paced Walk Test (FPWT, m/sec) before and immediately after the program. Pain intensity and health-related quality of life was self-reported before, immediately after, and at 12 months post-intervention using a visual analogue scale (VAS, 0–100) and the EQ-5D-5L index (−0.624 to 1.000), respectively. Associations of comorbidity combinations with change in outcomes immediately and at 12 months was estimated using mixed linear regression. Results: Individuals with OA improved on average 0.12 m/s (95%CI 0.12 to 0.13) in 40-m FPWT,  −12.7 mm (95%CI -13.2 to −12.2) in VAS, and 0.039 (95%CI 0.036 to 0.041) in EQ-5D-5L from before to immediately after the intervention with minor additional improvements at 12 months. Despite that individuals with comorbidities had worse baseline scores in all outcomes than individuals without comorbidities, they had similar levels of improvement immediately and 12 months after the intervention. Conclusion: Comorbidities are not associated with worse nor better health outcomes following an 8-week exercise and education program in individuals with OA, suggesting exercise as a viable treatment option for individuals with OA, irrespective of comorbidities.